Does prior mediastinal lymph node aspiration contribute to false-positive positron emission tomography–computed tomography?. Issue 4 (5th October 2020) - Ramsahai, J. Michael; Molnar, Christine; Lou, Lawrence; Ying, Winston; MacEachern, Paul; Hergott, Christopher A.; Dumoulin, Elaine; Strilchuk, Nadine; Fortin, Marc; Tremblay, Alain
Background: Proper staging of the mediastinum is an essential component of lung cancer evaluation. Positron emission tomography–computed tomography (PETCT) and endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA) are an integral part of this process. False-positive PETCT results can occur following surgical procedures but has not been demonstrated following EBUS-TBNA. We aimed to determine whether false-positive PETCT rates increase when EBUS-TBNA is performed prior to PETCT. Study design and methods: A retrospective review was carried out of clinical cases that underwent both PETCT and EBUS-TBNA within 30 days for the suspected malignancy. The impact of test sequence on the PETCT false-positive rate (FPR) was determined using Generalised Estimating Equation logistic regression analysis. Results: A total of 675 lymph node stations were sampled and imaged on PETCT. Overall, 332 (49.2%) nodes were sampled by EBUS-TBNA before PETCT, and 343 (50.8%) afterwards, with the interval between EBUS and subsequent PETCT being a mean±sd of 11.6±6.8 days (range 1–29). The FPR on qualitative PETCT for the EBUS first group was 41 (23.2%) out of 164, and for PETCT first it was 57 (29.0%) out of 193 for a difference of 5.8% (95% CI −3.4–14.7, p=0.22). In the regression model, EBUS as the first test was associated with a lower FPR when using the clinical PETCT interpretation. Interpretation: The performance of EBUS-TBNA sampling did not influence the FPR of PETCT when bronchoscopy took place in the 30 days prior to testing. Test sequence should be selected based on other clinical considerations. In patients with suspected malignancy undergoing endobronchial ultrasound transbronchial needle aspiration (TBNA) as well as PETCT scan, performing the TBNA prior to PETCT does not increase the rate of false-positive PET scan results https://bit.ly/3gFy6Fi